2006
DOI: 10.1080/01405110601080738
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy in a New Curriculum: Facilitating the Learning of Gross Anatomy using Web Access Streaming Dissection Videos

Abstract: As anatomy course hours have decreased, it has become increasingly important to provide tools that facilitate laboratory task efficiency. Digital video clips were created to present dissection guidance to medical students. The video clips communicate challenging aspects of the dissection process with succinct visual demonstrations easily accessed via an online course site. Students were asked to complete a survey designed to assess the quality and utility of the videos. Survey respondents indicated that the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 11 publications
3
58
0
Order By: Relevance
“…This method uses different techniques, e.g. : classical clinical PBL, clinical cases for medical students based on computed tomography scans, real patient clinical cases based on real patients' problems or documented case presentation of the tutorials in the form of patient/physician history taking and physical examination videos [11,14,15,46,49]. However, the interactive lectures seem to be the most sophisticated variants of the PBL method during which small-group tutorial sessions are integrated into each anatomical section and use anatomical models, bones, radiographs, and interactive 3-dimensional (3D) images [18].…”
Section: Category 3 Other (Problem-based Learning and Visualisation)mentioning
confidence: 99%
See 1 more Smart Citation
“…This method uses different techniques, e.g. : classical clinical PBL, clinical cases for medical students based on computed tomography scans, real patient clinical cases based on real patients' problems or documented case presentation of the tutorials in the form of patient/physician history taking and physical examination videos [11,14,15,46,49]. However, the interactive lectures seem to be the most sophisticated variants of the PBL method during which small-group tutorial sessions are integrated into each anatomical section and use anatomical models, bones, radiographs, and interactive 3-dimensional (3D) images [18].…”
Section: Category 3 Other (Problem-based Learning and Visualisation)mentioning
confidence: 99%
“…Azer and Eizenberg [5] demonstrated that students reported that dissection increased understanding of anatomical structures, provided them with a 3D perspective and helped them recall what they learnt. On the other hand, there are publications indicating that videos or clinical PBL improved the quality of the anatomy course [14,50].…”
Section: Category 2 Simulator Based Educationmentioning
confidence: 99%
“…A study in 2001 showed that video reviewing by third-year medical students resulted in higher test scores in pelvic anatomy (Sultana et al, 2001). Utilization of dissection clips has enhanced the quality and performance of students in gross anatomy (Pereira et al, 2004;DiLullo et al, 2006) and significantly brought about higher anatomy achievement scores in students with access to videos as compared to historical controls (Saxena et al, 2008).…”
Section: Computer Assisted Instruction (Cai)mentioning
confidence: 99%
“…Regardless of the method of assessment, almost all studies reported high satisfaction and increased knowledge after intervention. Student self-assessment typically revealed positive attitudes toward online lectures as a teaching modality [7,8,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Moreover, students showed increased knowledge in the subject material at hand, as evaluated by pre-and post-lecture knowledge assessment [11,[13][14][15]17,19,21,22,24,25,27,[29][30][31][32].…”
Section: Assessment Of Learning Outcomesmentioning
confidence: 99%